2022
DOI: 10.1111/1365-2745.13985
|View full text |Cite
|
Sign up to set email alerts
|

Divergent nitrogen and phosphorus allocation strategies in terrestrial plant leaves and fine roots: A global meta‐analysis

Abstract: 1. The quantification of the allocation of nitrogen (N) and phosphorus (P) among plant organs is essential to improve our understanding of plant growth, lifehistory strategies and ecosystem nutrient and energy cycles. However, allocation strategies of N and P between terrestrial plant leaves and fine roots are unclear.2. Here, we compiled a global dataset comprising 807 terrestrial plant species to analyse the stoichiometric scaling of N and P between leaves and fine roots across species, families, plant group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 98 publications
(165 reference statements)
1
9
0
Order By: Relevance
“…The dual pathways of nitrate assimilation could influence the assessment of root absorption and leaf resorption, and thus obscure their linkages. Third, the N and P allocation strategy diverges between the above‐ and below‐ground plant organs (Wang et al, 2022). More N is allocated to roots than to leaves, and the reverse is the case for P (Wang et al, 2022), possibly because the phloem in roots needs higher levels of N to support the required levels of photosynthate transport (Kerkhoff et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dual pathways of nitrate assimilation could influence the assessment of root absorption and leaf resorption, and thus obscure their linkages. Third, the N and P allocation strategy diverges between the above‐ and below‐ground plant organs (Wang et al, 2022). More N is allocated to roots than to leaves, and the reverse is the case for P (Wang et al, 2022), possibly because the phloem in roots needs higher levels of N to support the required levels of photosynthate transport (Kerkhoff et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the N and P allocation strategy diverges between the above‐ and below‐ground plant organs (Wang et al, 2022). More N is allocated to roots than to leaves, and the reverse is the case for P (Wang et al, 2022), possibly because the phloem in roots needs higher levels of N to support the required levels of photosynthate transport (Kerkhoff et al, 2006). Such an N allocation strategy implies that N could be obtained mostly by root absorption rather than leaf resorption, leading to discontinuity in the N economy.…”
Section: Discussionmentioning
confidence: 99%
“…For nutrient aboveground–belowground coordination, a recent global review indicated greater coordination of leaf with root N : P ratios in tropical forests relative to most other biomes, likely related to widespread tropical soil P scarcity and conservation of P in plant tissues (Wang et al ., 2022). A broad‐scale paper linking remotely sense canopy traits in Panama with soil data found that canopy greenness (a surrogate for NPP) corresponded to variations in soil fertility and toxicity (Fisher et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon (C), nitrogen (N), and phosphorus (P) are major macro elements necessary for life (Elser et al, 2000); their cycling in plant leaves-litter-soil systems has substantial effects on the function and stability of ecosystems. Due to the important function of N and P (Wang et al, 2022), previous studies generally pay more attention to the resorption efficiency of N (NRE) and P (PRE).…”
Section: Introductionmentioning
confidence: 99%